Investigation Into E-Retailing Industry's Prevailing Competitive Forces - Hoi, Chong Sek (2000)
This exploratory research report written based on a content analysis being done on top 10 e-retailing companies' strategic directions, problems encountered and observed threats. The study explored the crucial competitive forces determining the competitive structure in e-retailing industry, strategy and common threat observed.